2017
DOI: 10.1182/blood-2017-05-786699
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the clinical phenotype and pathophysiology underlying low VWF levels

Abstract: Critical clinical questions remain unanswered regarding diagnosis and management of patients with low von Willebrand factor (VWF) levels (30-50 IU/dL). To address these questions, the Low VWF Ireland Cohort (LoVIC) study investigated 126 patients registered with low VWF levels. Despite marginally reduced plasma VWF levels, International Society of Thrombosis and Haemostasis Bleeding Assessment Tool (ISTH BAT) confirmed significant bleeding phenotypes in the majority of LoVIC patients. Importantly, bleeding ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
238
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(261 citation statements)
references
References 54 publications
22
238
1
Order By: Relevance
“…It is unclear why the majority (91%) of cases are female given that the bleeding score was similar after the female specific bleeding issues (PPH and menorrhagia) had been deducted. It is known from an Irish study of 126 patients, with low VWF (0.3‐0.5 IU/mL), that 89% were women and the median age was 39 and that when gynaecological bleeding was removed the bleeding score remained elevated, which resembles our collection . Mean age of presentation was 38.4 years (men 33.2, women 38.8; Table ).…”
Section: Discussionsupporting
confidence: 58%
“…It is unclear why the majority (91%) of cases are female given that the bleeding score was similar after the female specific bleeding issues (PPH and menorrhagia) had been deducted. It is known from an Irish study of 126 patients, with low VWF (0.3‐0.5 IU/mL), that 89% were women and the median age was 39 and that when gynaecological bleeding was removed the bleeding score remained elevated, which resembles our collection . Mean age of presentation was 38.4 years (men 33.2, women 38.8; Table ).…”
Section: Discussionsupporting
confidence: 58%
“…Consistently, only 65–75% of the patients with plasma VWF < 30 IU dL −1 have VWF sequence variations, and this frequency decreases progressively as the VWF level rises to > 30 IU dL −1 . A recent study in unequivocal bleeders with ‘low VWF’ (30–50 IU dL −1 ) found no correlation between BS and VWF levels, and most patients had normal VWF propeptide/VWF:Ag ratios and sustained response of VWF:Ag and VWF:RCo to desmopressin (DDAVP), consistent with decreased VWF synthesis or secretion . This suggests that most bleeders with ‘low VWF’ have type 1 VWD, and are not just individuals with VWF situated within the 2.5th percentile distribution .…”
Section: Difficulties With Diagnosis Of Type 1vwdmentioning
confidence: 99%
“…Conversely, moderately reduced VWF levels (35‐50 IU/dL) show low heritability, rarely exhibit linkage to the VWF locus, and are not always associated with significant bleeding . However, data from the Low VWF Ireland Cohort (LoVIC) study shows that 77% of females with VWF levels between 30 and 50 IU/dL had positive ISTH‐BAT scores . The latter highlights the gender differences with respect to the diagnosis of VWD.…”
Section: Type 1 Vwd Vs ‘Possible or Low Vwf’mentioning
confidence: 99%
“…A recent publication looked at predictors of VWD diagnosis for those individuals with borderline VWF levels (30‐60 IU/dL) . The authors used a multivariable logistic regression model which was fitted with gender, age, bleeding score, family history, VWF:RCo and ABO blood group as predictors, to predict VWD diagnosis.…”
Section: Type 1 Vwd Vs ‘Possible or Low Vwf’mentioning
confidence: 99%